Improvement of cell suspension cultures of transformed and untransformed Carica papaya cell lines, towards the development of an antiparasitic product against the gastrointestinal nematode Haemonchus contortus - Ortiz Caltempa, Anabel; Hernández, Marisela; Pérez, Ana Lilia; Aguilar, Liliana; Guzmán, Cynthia; Ayón-Núñez, Dolores Adriana; Fragoso, Gladis; Bobes, Raúl J.; López, Maria Eugenia; Sciutto, Edda; Villareal, María Luisa (Frontiers in Cellular and Infection Microbiology, 2022)
Parasitic diseases highly impact human and animal health worldwide. Despite the availability of effective anti-parasitic drugs their excessive and uncontrolled use has promoted the emergence of drug resistance and negatively impact on ecosystems and human health. Thus, it is necessary to develop an environmental friendliness antiparasitic treatments. Carica papaya has been documented as an alternative option to treat infectious diseases. In our research group Carica papaya embryogenic callus were employed to genetically insert immunogenic peptides to develop an oral anti-cysticercosis vaccine. One of these callus cell line (CF-23) that express the KETc7 immunogenic peptide induced high level of protection against experimental cysticercosis. Towards the generation of a natural Carica papaya based antiparasitic product, that simultaneously induced immunity against cysticercosis, the development and optimization of the transformed (SF-23) and untransformed (SF-WT) suspension cultures was performed. The obtained results showed better kinetic parameters of duplication time (td) for SF-23 (6.9 days), than for SF-WT (13.02 days), which guide the selection of SF-23 line to be scaled-up in a 2 L airlift bioreactor where a duplication time of 4.4 days was reached. For the first time a transgenic line of Carica papaya has been grown in an airlift bioreactor, underlying its potential for a scaled-up cultivation in this type of reactor. The nematicidal activity against Haemonchus contortus of aqueous extracts of SF-WT and SF-23 began to be explored in this work, with promising results. The obtained information is valuable to continue the cultivation of the transgenic cell suspension line of Carica papaya under reproducible conditions, towards the development of a new anti-parasitic product.